GAMBARAN PENGETAHUAN HIV/AIDS PADA IBU RUMAH TANGGA DI DESA SAMBIRENTENG KECAMATAN TEJAKULA KABUPATEN BULELENG TAHUN 2020 - Rini Winangsih; Made Dewi Sariyani (STIKES ADVAITA MEDIKA TABANAN, 2021)
Abstract - Human Immunodeficiency Virus Acquired Immunodeficiency Syndrome (HIV / AIDS) is a disease caused by HIV infection. HIV itself is a virus that causes immunodeficiency or immune system disorders in humans. The purpose of this study was to describe the knowledge of housewives about HIV / AIDS in Sambirenteng Village, Tejakula District, Buleleng Regency, Bali. The research methodology used is descriptive method with a cross-sectional design which was implemented in Sambirenteng Village, Tejakula District in August 2020. The sample in this study were housewives who live in Sambirenteng Village, Tejakula District, as many as 95 people and were taken by simple random sampling technique. The instrument in this study used a questionnaire distributed online. Data analysis techniques using univariate analysis. The results of this study included the level of knowledge of housewives about HIV / AIDS in Sambirenteng Village, most of them were in the good category, as many as 91 respondents (95.8%). So, the conclusion in this study is that the method of outreach through social media with unique teaching aids is necessary to make it easier for mothers to understand about HIV / AIDS in depth. Suggestion The description of housewives' knowledge about HIV / AIDS can be used as a reference in further research.